2022
DOI: 10.3390/f13070990
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Plant Seedling Functional Traits Suggest Lianas Also Support “Fast-Slow” Plant Economics Spectrum

Abstract: Lianas are predicted to perform better than trees during seasonal drought among tropical forests, which has substantial implications for tree and forest dynamics. Here, we use whole-plant trait comparison to test whether lianas allocated on the resource acquisitive end of the continuum of woody plant strategies. We measured morphological and biomass allocation traits for seedlings of 153 species of trees and lianas occurring in a tropical forest in Thailand during the dry season. We first compared trait differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…(Apocynaceae) and Paullinia pinnata (Sapindaceae). An abundance of liana relative to tree seedlings corroborates reports from other tropical forests that liana density is disproportionally increasing (Schnitzer et al, 2012;Sun et al, 2022), with potentially adverse consequences for trees (Schnitzer and Bongers, 2011;Venegas-González et al, 2020), but see Umaña et al (2020). One explanation for an increase in liana seedlings could be a seasonal growth advantage (SGA), because lianas are able to grow faster than trees during seasonal drought (Sun et al, 2022 and references within).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…(Apocynaceae) and Paullinia pinnata (Sapindaceae). An abundance of liana relative to tree seedlings corroborates reports from other tropical forests that liana density is disproportionally increasing (Schnitzer et al, 2012;Sun et al, 2022), with potentially adverse consequences for trees (Schnitzer and Bongers, 2011;Venegas-González et al, 2020), but see Umaña et al (2020). One explanation for an increase in liana seedlings could be a seasonal growth advantage (SGA), because lianas are able to grow faster than trees during seasonal drought (Sun et al, 2022 and references within).…”
Section: Discussionsupporting
confidence: 76%
“…One explanation for an increase in liana seedlings could be a seasonal growth advantage (SGA), because lianas are able to grow faster than trees during seasonal drought (Sun et al, 2022 and references within). However, while this may be the case for adult lianas (Sun et al, 2022), to what extent this applies to seedlings is unclear and results are mixed. Ledo and Schnitzer (2014) and Umaña et al (2019) found that liana seedlings did benefit from dry conditions and disturbance, Vogado et al (2022) attributed increasing liana abundances to increased CO 2 concentrations, while light availability has been found to be more important for liana seedling survival in some other studies (Addo-Fordjour and Rahmad, 2015;De Campos Franci et al, 2016).…”
Section: Discussionmentioning
confidence: 99%